Stereotactic body radiation therapy for colorectal liver metastases. (31st December 2022) - Mohamad, Issa; Barry, Aisling; Dawson, Laura; Hosni, Ali
Abstract: Multidisciplinary case discussion of patients with colorectal liver metastases (CRLM) has led to improved selection of more complex patients with the oligometastatic disease for treatment with surgical resection, locally ablative therapy or a combination of local modalities to improve the therapeutic ratio in patients with CRLM. Stereotactic body radiation therapy (SBRT) is a noninvasive local therapy with a potential role in the management of oligometastatic CRLM and may be considered as an alternate choice to other locally ablative therapies like radiofrequency ablation, radioembolization, chemoembolization or surgery or after the failure of other local treatment or in combination with surgery. Existing evidence reports for highly selected patients with CRLM, one to five fractions SBRT can be delivered safely, with satisfactory long-term local control, overall survival and quality of life. This review article will present the evidence of SBRT in this setting.